2019
DOI: 10.1108/intr-03-2018-0113
|View full text |Cite
|
Sign up to set email alerts
|

Sharing economy: seeing through the fog

Abstract: Emerald allows authors to deposit their AAM under the Creative Commons Attribution Non-commercial International Licence 4.0 (CC BY-NC 4.0). To do this, the deposit must clearly state that the AAM is deposited under this licence and that any reuse is allowed in accordance with the terms outlined by the licence. To reuse the AAM for commercial purposes, permission should be sought by contacting permissions@emeraldinsight.com.For the sake of clarity, commercial usage would be considered as, but not limited to:• C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…Among the various reasons for this MSP's social innovation trajectory, we demonstrated that when MSPs, such as Airbnb, increase their size, they become a disruptive competitor for existing businesses and can thus be considered as disruptors in the corresponding markets (Trabucchi et al, 2019). That is why they are often called, by several institutional and non‐institutional actors, to reach a sustainable growth by reducing their negative impacts on society (i.e., both industry and market sides).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various reasons for this MSP's social innovation trajectory, we demonstrated that when MSPs, such as Airbnb, increase their size, they become a disruptive competitor for existing businesses and can thus be considered as disruptors in the corresponding markets (Trabucchi et al, 2019). That is why they are often called, by several institutional and non‐institutional actors, to reach a sustainable growth by reducing their negative impacts on society (i.e., both industry and market sides).…”
Section: Discussionmentioning
confidence: 99%
“…However, these possibilities are questionable, as the sharing economy can increase overall load on the environment through higher consumption (Frenken & Schor, 2017). Several archetypes of sharing economy businesses are proliferating nowadays (Trabucchi, Muzellec, & Ronteau, 2019) and a number of startups are increasingly leveraging this approach in their innovative BMs (Sanasi, Ghezzi, Cavallo, & Rangone, 2020), thus generating relevant effects on existing industries (Roma, Panniello, & Lo Nigro, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This mechanism has been highly studied in specific fields that often rely on the structure of a two or a multisided platform, such as sharing economy (e.g. Sanasi, Cavallo, Ghezzi & Rangone, 2020; Trabucchi, Muzellec, & Ronteau, 2019) and crowdsourcing (e.g. Täuscher, 2019; Täuscher, Bouncken, & Pesch, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The previously mentioned Uber, Airbnb and Coursera, but also Facebook, YouTube, Deliveroo, Etsy and the less recent eBay, or Booking.com, are all two‐sided or multisided platforms. Most of them are digital companies mainly focusing on the service field; nevertheless, recent research is showing how two‐sided or multisided platforms are having an impact in many different industries with the spread of the sharing economy (Geissinger, Laurell, & Sandström, 2018; Sanasi, Ghezzi, Cavallo, & Rangone, 2020; Trabucchi, Muzellec, & Ronteau, 2019), in the brick and mortar industries (Daiberl, Oks, Roth, Möslein, & Alter, 2019), and even influencing urbanisms owing to the change of habits of the inhabitants, for example, regarding the car sharing phenomenon (Caprotti & Liu, 2019). Some evidence in recent literature highlights the fact that relevant disruptors currently relying on two‐sided or multisided platforms were originally based on linear value chains.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, academic-and practitioner-oriented literatures have paid a lot of attention to these platforms, which have been highly boosted by the spread of digital technologies, since these are highly appreciated by investors (Trabucchi et al, 2019;Sanasi et al, 2020). Moreover, this kind of platforms has been highly studied in the field of crowdsourcing, matching people asking and offering knowledge on given topics (e.g., Randhawa et al, 2017;Malhotra and Majchrzak, 2020) Platforms emerged as a new business model (Amit and Han, 2017), for various reasons, and offering various opportunities.…”
Section: Theoretical Background: the Superpowers Of Platformsmentioning
confidence: 99%